Expectations Management and Beatable Targets: How Do Analysts React to Explicit Earnings Guidance?* - Cotter, Julie; Tuna, Irem; Wysocki, Peter D. (Contemporary Accounting Research, 2006)
This study investigates security analysts' reactions to public management guidance and assesses whether managers successfully guide analysts toward beatable earnings targets. We use a panel data set between 1995 and 2001 to examine the fiscal‐quarter‐specific determinants of management guidance and the timing, extent, and outcomes of analysts' reactions to this guidance. We find that management guidance is more likely when analysts' initial forecasts are optimistic, and, after controlling for the level of this optimism, when analysts' forecast dispersion is low. Analysts quickly react to management guidance and are more likely to issue final meetable or beatable earnings targets when management provides public guidance. Our evidence suggests that public management guidance plays an important role in leading analysts toward achievable earnings targets.